Family law in practice - Inns of Court School of Law. Institute of Law City University London (Oxford University Press, 2004)
This manual therefore provides a detailed introduction to the key areas of the substantive family law of which the junior practitioner should have a good working knowledge. Key aspects of family law covered include domestic violence, occupation of the family home, care proceedings, ancillary relief and orders under s8 Children Act 1989. In recognition of the increasing desire to avoid costly and lengthy adversarial proceedings, the manual also includes a dedicated chapter focusing specifically on the role of mediation as a tool to resolving family law disputes